Analysis of European Union Non-Tariff Trade Barriers on Crude Palm Oil Imports from Indonesia - Bangun, Siti Zainurrahmi Br; Ridho, Muhammad Rasyid (Strata Social and Humanities Studies, 2025)
This study examines the impact of the European Union's non-tariff trade barriers on Indonesia's crude palm oil (CPO) exports, focusing on the Renewable Energy Directive (RED) and its successor, RED II. Despite palm oil's global competitiveness due to its cost-efficiency, high yield, and multifunctional applications, the EU has increasingly restricted its imports by citing environmental concerns, particularly related to deforestation and greenhouse gas emissions. Using a qualitative case study approach, this research analyzes the form and rationale behind EU trade policies, drawing on primary and secondary data, including official government reports, stakeholder interviews, and document analysis. The study finds that RED II and its implementing regulations, such as the Delegated Act 2019, function as de facto trade barriers that significantly constrain Indonesia’s CPO export performance. These measures reflect a policy shift prioritizing sustainability and climate goals, often to the detriment of Indonesian trade interests. The findings underscore the need for Indonesia to strengthen its palm oil diplomacy, enhance the transparency of sustainability certifications, align with international standards, and diversify export destinations. This research contributes to a deeper understanding of international trade dynamics and offers strategic insights for future trade negotiations.